Diversitas Serangga Permukaan Tanah Pada Lokasi Budidaya Padi Sasak Jalan Di Loa Duri Kabupaten Kutai Kartanegara - Nurmianti, Nurmianti; Hariani, Nova; Budima, Budima (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2015)
Explorative descriptive research that has been implemented inpaddy-fields at Sasak jalan aim to understand diversity andstructure of the community an insect active in the surface of theground. Insects was collected by pitfall trap method.The resultshowed, there were 7 ordo, 14 famili and 18 genus of insects inthe paddy fields sasak jalan. The diversity of the average rangedfrom 0.78-0.84. Index of uniformity in each paddy field rangedbetween 0.66-0,75 with the highest uniformity index waslocated on the land of the zone I to the value of 0.75. Indexdominance in each land, averaging around between 0.18-0.23.